Reflections on the T Trials. (17th October 2020) - Swerdloff, Ronald; Wang, Christina
Abstract: Background: This manuscript is a review and discussion of the published results of the T Trials. Objective: To re‐examine the efficacy of testosterone replacement of hypogonadal men >65 years of age in the T Trials. Materials and Methods: The T Trials were a complex collection of seven double blind, placebo‐controlled trials of the efficacy of testosterone as replacement therapy for older men with unequivocal hypogonadism. There were three main trials (sexual function; physical function; vitality) and four sub‐trials (cognition; bone; anemia; and cardiovascular). All subjects participated in the main trials while more selective inclusion/exclusion criteria existed for the sub‐trials. Subjects were excluded for perceived higher risk of prostate cancer and recent myocardial or cerebral vascular events. Results: The previously published results are reviewed here as seen in the context of this special issue on late‐onset hypogonadism. In the T Trials, positive benefits were seen in the sexual function, bone, and anemia trials with small but significant benefits in the vitality trial. No benefit was seen in the cognition trial, partial benefit in physical function, and a negative benefit outcome seen in the cardiovascular trial. The later trial was underpowered and the results were described as exploratory. Adverse events were relatively uncommon in the 12‐month treatment phase and additional 12‐month post‐treatment phase. The most frequent adverse effect ascribed to testosterone was erythrocytosis. Conclusions: The T Trials studied the efficacy of testosterone replacement therapy on 788 men with low testosterone and symptoms of hypogonadism. The studies demonstrated benefits in four trials (sexual function, vitality, bone, and anemia); partial benefit in the physical function trial; no effect in the cognition trial; and a negative effect in the exploratory cardiovascular trial. The T Trials were not designed to assess long‐term risks of testosterone in men.